2013
DOI: 10.1002/pola.27071
|View full text |Cite
|
Sign up to set email alerts
|

Controlled/living polymerization of methyl methacrylate using new sterically hindered imidazoline nitroxides prepared via intramolecular 1,3-dipolar cycloaddition reaction

Abstract: A series of imidazoline nitroxides with bulky spirocyclic moieties at the positions 2 or 5 of imidazole ring were synthesized using intramolecular 1,3-dipolar cycloaddition in 2Himidazole 1-oxides or 4H-imidazole 3-oxides with pent-4-enyl groups followed by isoxazolidine ring opening and oxidation. Capability of the nitroxides to control radical polymerization of methyl methacrylate (MMA) and styrene was investigated. For that purpose, alkoxyamines were synthesized from the aforementioned nitroxides and tert-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…We have recently reported on similar reversibility of intramolecular cyclization of sterically shielded pent-4-enylnitrone of 2H-imidazole series [15]. We have previously reported that H2O2/WO4 2system is inefficient for the oxidation of secondary amines with spiro-(2-hydroxymethyl)-cyclopentane moiety at α-carbon to nitroxides, while this oxidation can be easily performed using m-CPBA [6,15].…”
Section: Scheme 4: Intramolecular 13-dipolar Cycloaddition Of Alkenymentioning
confidence: 97%
“…We have recently reported on similar reversibility of intramolecular cyclization of sterically shielded pent-4-enylnitrone of 2H-imidazole series [15]. We have previously reported that H2O2/WO4 2system is inefficient for the oxidation of secondary amines with spiro-(2-hydroxymethyl)-cyclopentane moiety at α-carbon to nitroxides, while this oxidation can be easily performed using m-CPBA [6,15].…”
Section: Scheme 4: Intramolecular 13-dipolar Cycloaddition Of Alkenymentioning
confidence: 97%
“…Considering previous results showing that a sterically hindered imidazoline nitroxide has a low k cD value but also a low stability, several imidazoline nitroxides and their corresponding alkoxyamines bearing a spiro cyclic moiety were prepared via 1,3‐dipolar cycloaddition reaction, enabling the facile synthesis of a library of compounds (Figure a) . The fraction of disproportionation was found to be low (1.3–3%), making these materials potential initiators for NMP of methacrylic esters.…”
Section: Nmp Of Mma: Why Does It Fail?mentioning
confidence: 92%
“…b) Evolution of M n and D‐ with monomer conversion for NMP of MMA initiated with an ethyl‐based alkoxyamine at 80 °C with a monomer‐to‐initiator ratio of 800:1. Reproduced with permission …”
Section: Nmp Of Mma: Why Does It Fail?mentioning
confidence: 99%
“…The processes belonging to the first group are based on the reaction of a reversible polymerization break during the interaction of a growing radical with specially introduced regulating agents (Scheme 1). These include polymerization by the mechanism of reversible inhibition [27][28][29] and atom transfer polymerization [25,[30][31][32]. The second group of methods includes processes in which the exchange between active and dormant chains occurs due to degenerate chain transfer:…”
Section: Synthesis Of Pan Precursor Under Conditions Of Controlled Ramentioning
confidence: 99%
“…As is known [27][28][29], one of the directions of the CRP in terms of the mechanism of reversible inhibition is associated with the use of nitroxyl radicals generated in situ (directly in the reaction system) from available precursors to control the polymerization. The indicated approach was successfully used for the synthesis of AN copolymers [78].…”
Section: № 2 (7) 2019mentioning
confidence: 99%